2013
DOI: 10.1080/07391102.2012.706075
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies on New Delhi Metallo-β-lactamase (NDM-2) suggest old β-lactam, penicillin to be better antibiotic for NDM-2-harbouringAcinetobacter baumanni

Abstract: Acinetobacter baumannii, a Gram-negative pathogen causes nosocomial infections including pneumonia, urinary tract and respiratory infections. Carbapenem group of β-lactam antibiotics are routinely used to treat A. baumannii including multidrug-resistant clinical strains. The emergence of New Delhi Metallo-β-lactamase (NDM-2), a new type of β-lactamase and one of the major resistant determinants in A. baumannii, opened up challenges in the treatment of resistant strains. Thus, understanding the structure-functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 41 publications
(50 reference statements)
0
16
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13][14] Hospital-acquired infections are associated with high mortality and morbidity rates 15,16 ; hence, their prevention and cure are urgently needed. [4][5][6][7][8][9][10][11][12][13][14] Hospital-acquired infections are associated with high mortality and morbidity rates 15,16 ; hence, their prevention and cure are urgently needed.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14] Hospital-acquired infections are associated with high mortality and morbidity rates 15,16 ; hence, their prevention and cure are urgently needed. [4][5][6][7][8][9][10][11][12][13][14] Hospital-acquired infections are associated with high mortality and morbidity rates 15,16 ; hence, their prevention and cure are urgently needed.…”
mentioning
confidence: 99%
“…Proteomic study of outer membrane of the E. coli revealed over expression FhuE and FhuA, and YbiL that have role in the iron transport [119]. By differential proteomics study, the role of iron in the continued existence of A. baumannii resistance strain (ATCC and carbapenem) in human host is revealed [120,121]. Proteome of the human host changes during Acinetobacter baumannii infection.…”
Section: Significance Of Omv Proteomics In Virulence Of Pathogensmentioning
confidence: 99%
“…Role of proteins detected by the quantitative proteomics methods has been validated by other in-vitro or in-vivo methods. It was found that Acinetobacter baumannii develop resistance against carbapenem via alteration in the expression/activity of β-lactamase (Tiwari et al, 2012a,b,c; Tiwari, 2013, 2014; Tiwari and Moganty, 2013, 2014) and alteration in the penicillin binding protein (Vashist et al, 2011). Upregulation of metabolic enzymes/proteins found in the inner membrane protein also enhanced the carbapenem resistance in A. baumannii (Tiwari et al, 2012c).…”
Section: Quantitative Proteomics As a Tool To Study Of Carbapenem Resmentioning
confidence: 99%